Towards healthier and more sustainable diets in the Australian context: comparison of current diets with the Australian Dietary Guidelines and the EAT-Lancet Planetary Health Diet - Gilly A. Hendrie; Megan A. Rebuli; Genevieve James-Martin; Danielle L. Baird; Jessica R. Bogard; Anita S. Lawrence; Bradley Ridoutt (BMC, 2022)
Abstract Background There is increasing focus on moving populations towards healthier and more environmentally sustainable dietary patterns. The Australian Dietary Guidelines provide dietary patterns that promote health and wellbeing. It is unclear how these guidelines align with the more recently published global recommendations of the EAT-Lancet Planetary Health Reference Diet, and how Australian diets compare to both sets of recommendations. Methods Data from one 24-h recall collected for the 2011-13 National Nutrition and Physical Activity Survey were analysed for 5,920 adults aged 19-50 years. Subgroups of this population were identified by diet quality and lower or higher consumption of foods often considered to be environmentally intensive (higher animal meat and dairy foods) or associated with healthiness (higher vegetables and lower discretionary choices). Food group and nutrient composition of Australian diets were compared to diets modelled on the Australian Dietary Guidelines and Planetary Health Reference Diet. The environmental impacts of diets were estimated using an index of combined metrics. Results Compared with the Planetary Health Reference Diet, the Australian Dietary Guidelines contained more servings of the vegetable, dairy and alternatives, fruit, and discretionary choices. The amount of meat and alternatives was higher in the Planetary Health Reference Diet than Australian Dietary Guidelines due to the inclusion of more plant-based meat alternatives. The average Australian diet contained two to almost four times the Australian Dietary Guidelines and Planetary Health Reference Diet maximum recommended intake of discretionary choices, and provided inadequate amounts of the vegetables, cereals, unsaturated fats and meats and alternatives food groups, primarily due to lower intakes of plant-based alternatives. The average Australian diet also contained less dairy and alternatives than the Australian Dietary Guidelines. In the average Australian diet, red meat and poultry contributed 73% to the total servings of meat and alternatives compared to 33% and 10% for the Australian Dietary Guidelines and Planetary Health Reference Diet respectively. The modelled Australian Dietary Guidelines diet met the relevant nutrient reference value for all 22 nutrients examined, whereas the Planetary Health Reference Diet contained an inadequate amount of calcium. The environmental impact scores of the Planetary Health Reference Diet and Australian Dietary Guidelines were 31% and 46% lower than the average Australian diet. Conclusions Significant changes are required for Australians' dietary intake to align more closely with national and global dietary recommendations for health and environmental sustainability.